Manure studies in the Ethiopian highlands: II. Effect on Medicago sativa L. and Desmodium uncinatum grown on an ultisol - Saka, A.R.; Haque, I. (International Livestock Centre for Africa, 1993)
This document reports on the results of two experiments which investigted the effects of manure on alfalfa and desmodium grown on an Ultisol at Soddo in Sidamo region. The experiments were conducted to determine the effects of cattle manure on dry matter yields and on nutrient uptake by alfalfa and desomdium, to investigate soil-water storage and transmission characteristics in an acid red soil (Ultisol) grown to alfalfa as influenced by cattle manure, to investigate the effects of cattle manure on soil chemical properties of an acid res soil (Ultisol), and to correlate dry matter yields and nutrient uptake with plant tissue nutrient concentration and soil chemical properties.